2014
DOI: 10.1111/1471-0528.12706
|View full text |Cite
|
Sign up to set email alerts
|

Are women having a vaginal birth after a previous caesarean delivery at increased risk of anal sphincter injury?

Abstract: Objective To examine the incidence of obstetric anal sphincter injury in women who had a successful vaginal birth after a previous caesarean delivery (VBAC).Design Retrospective analysis of prospectively gathered data.Setting A tertiary referral university institution.Population All secundiparous women with a previous caesarean delivery who had a VBAC from 2001 to 2011.Methods Details of maternal demographics, intrapartum characteristics and outcomes were examined in cases of VBAC with accompanying anal sphinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 19 publications
(18 reference statements)
6
60
5
Order By: Relevance
“…The prevalence of severe perineal trauma among nulliparous women in this study was 7.0%, which is confirmed by statistics from the Swedish National Board of Welfare for this time period. 10 Our findings did not support this theory of Hehir, as women in our sample who had a primary cesarean at full dilation had a similar risk of severe perineal trauma as women with a planned primary cesarean delivery. 6,[9][10][11][12] The explanation for the elevated risk among women undergoing VBAC remains unclear, but previous theories have focused on the characteristics of primary cesarean delivery.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The prevalence of severe perineal trauma among nulliparous women in this study was 7.0%, which is confirmed by statistics from the Swedish National Board of Welfare for this time period. 10 Our findings did not support this theory of Hehir, as women in our sample who had a primary cesarean at full dilation had a similar risk of severe perineal trauma as women with a planned primary cesarean delivery. 6,[9][10][11][12] The explanation for the elevated risk among women undergoing VBAC remains unclear, but previous theories have focused on the characteristics of primary cesarean delivery.…”
Section: Discussioncontrasting
confidence: 80%
“…Characteristics of primary cesarean section such as indication or timing of delivery, birthweight of first child, or interpregnancy interval did not alter the risk level of severe perineal trauma. Hehir et al 10 reported that "a large number" of women with severe perineal trauma in a subsequent vaginal delivery had progressed to an advanced stage before delivering by primary cesarean section (n = 27/60). 13 The rate of 12.3% severe perineal trauma among women undergoing VBAC in this study is within the range of 1.8%-18% reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the OASIS complicates 1.3% of natural vaginal deliveries, 3.7% of vacuum deliveries and 8.6% of forceps deliveries . Numerous studies have attempted to identify risk factors associated with OASIS following vaginal delivery of singletons . However, there has been little research involving multiple pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…studies have attempted to identify risk factors associated with OASIS following vaginal delivery of singletons. 4,5 However, there has been little research involving multiple pregnancies. Given the constant rise in twin deliveries, largely due to the increase in assisted reproductive techniques, 6 it is important to estimate perineal trauma rates in these deliveries.…”
mentioning
confidence: 99%